Air pollution and health - Hester, R. E.; Harrison, Roy M., 1948- (Royal Society of Chemistry, 1998)
The impact of air pollution on human health is currently of international concern. A comprehensive review of the subject is given in this volume, which complements the previous title covering air quality management. Dealing with the common gaseous and particulate air pollutants, including chemical carcinogens, it reviews the epidemiological and exposure chamber study research as well as considering mechanistic studies in the case of particulate matter. Air Pollution and Health also addresses the practical issue of setting standards for human exposure to air pollution by including the philosophy of standard setting and a review of currently available standards, along with a description of the setting of USEPA revised standards for ozone and particulate matter. Current knowledge of indoor air pollution is also discussed. As with all other books in the series, this volume will be of interest to the general public as well as being an important reference source for all those involved in the field, be it as student, industrialist, government agent, or health professional.
Keywords: Air -- Pollution -- Physiological effect.; elektronické knihy; electronic books